2009
DOI: 10.3746/jkfn.2009.38.12.1760
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Yukwa Base According to the Extrusion Processing Conditions (Ⅰ): Manufacturing of Yukwa Base with Combination of Glutinous Rice Flour and Rice Flour

Abstract: Physical properties of Yukwa base extruded with glutinous rice flour, rice flour, defatted soy flour, and salt using an twin-screw extruder were investigated. The ingredients were extruded at various moisture contents (16~18%), screw speeds (300 & 400 rpm) at 43.4 kg/hr feed rate. Length and specific volume of Yukwa base increased with decreasing moisture contents. Hunter's color L * values of Yukwa base was higher whereas a * and b * values were lower with increasing moisture content. Water absorption index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Additionally, Kim and Ryu (2001) reported that with extrusion conditions of 20-27% moisture content, 2.76 MPa CO 2 gas injection pressure, and 200 rpm screw speed, yukwa puffed by the microwave oven method had low density and soft texture. Eun et al (2009) investigated yukwa extruded with glutinous rice flour, rice flour, defatted soy flour, and salt using a twin-screw extruder, finding that feed moisture content had a significant influence on the physical properties of yukwa bases. Lee et al (2007) concluded that extrusion puffing technology could be adopted as an alternative to conventional deep-fat frying as a partial manufacturing process of yukwa.…”
mentioning
confidence: 99%
“…Additionally, Kim and Ryu (2001) reported that with extrusion conditions of 20-27% moisture content, 2.76 MPa CO 2 gas injection pressure, and 200 rpm screw speed, yukwa puffed by the microwave oven method had low density and soft texture. Eun et al (2009) investigated yukwa extruded with glutinous rice flour, rice flour, defatted soy flour, and salt using a twin-screw extruder, finding that feed moisture content had a significant influence on the physical properties of yukwa bases. Lee et al (2007) concluded that extrusion puffing technology could be adopted as an alternative to conventional deep-fat frying as a partial manufacturing process of yukwa.…”
mentioning
confidence: 99%